ARBUSCULAR MYCORRHIZAL FUNGI INCREASED PLANT GROWTH AND NUTRIENT CONCENTRATIONS OF MILKWOOD TROPICAL TREE SPECIES Alstonia scholaris UNDER GREENHOUSE CONDITIONS - Turjaman, Maman; Santoso, Erdy; Tawaraya, Keitaro (Secretariat of Forestry Research and Development Agency, 2007)
The objective of this study was to determine the effect of five arbuscular mycorrhizal (AM) fungi on the early growth of Alstonia scholaris (milkwood) seedlings. The seedlings were inoculated with Glomus clarum Nicholson & Schenk, Gigaspora decipiens Hall & Abbott, Glomus sp. ACA Tulasne & Tulasne, Entrophospora sp. Ames & Scheneider, and Glomus sp. ZEA Tulasne & Tulasne, and uninoculated (control) under greenhouse conditions. Percentage of AM colonization, plant growth, survival rate, mycorrhizal dependency (MD), shoot nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), and magnesium (Mg) concentrations were measured after 150 days. Survival rates were higher in the AM-colonized seedlings at 150 days after transplantation than those in the control seedlings. Mycorrhizal Dependency (MD) values were 80, 78, 79, 78 and 78% in A. scholaris inoculated with G. clarum, G. decipiens, Glomus sp. ACA, Entrophospora sp., and Glomus sp. ZEA, respectively. Shoot N, P, K, Ca and Mg content of the seedlings were increased by AM fungi as much as 82-86, 81-86, 81-86, 88-91 and 85-90%, respectively. The percentage of AM colonization of A. scholaris ranged from 64 to 91 %. Colonization by five AM fungi increased plant height, diameter, total fresh weight, total dry weight and total length root. Glomus clarum was more effective in improving nutrient content and plant growth of A. scholaris than G. decipiens, Entrophospora sp., Glomus sp. ZEA and Glomus sp. ACA. Total root length of A. scholaris ranged from 1,180 to 1,310 cm. The results suggest that AM fungi can accelerate the establishment of the seedling stocks of A. scholaris. This finding would contribute to the effort of establishing A. scholaris plantation.